Breeding of virus-resistant transgenic sugarcane by the integration of the Pac1 gene - Wang, Wenzhi; Wang, Jungang; Feng, Xiaoyan; Shen, Llinbo; Feng, Cuilian; Zhao, Tingting; Xiao, Hong; Li, Shifang; Zhang, Shuzhen (Frontiers in Sustainable Food Systems, 2022)
Various RNA viral diseases on sugarcane result in yield loss and decreased sugar content. Breeding new varieties with virus resistance is the main goal of sugarcane breeding program. Both single-stranded and double-stranded RNA viruses generated a double-stranded RNA replicative form (RF) during the replication cycle progress. While double-stranded RNA-specific ribonuclease (PAC1) encoded by Pac1 gene (from Schizosaccharomyces pombe) can recognize and degrade double-stranded RNA specifically without any sequence specifically, the expression of PAC1 in transgenic sugarcane may successfully develop virus-resistant sugarcane. In this research, we firstly expressed the PAC1 in prokaryotic cells. Then, double-stranded RNA RF of sugarcane streak mosaic virus (SCSMV) were artificially synthesized. The degradation activity of the PAC1 was successfully tested by mixing the PAC1 protein and the double-stranded RNA RF. After that, the Pac1 gene was ligated to a plant expression vector,and were then introduced into a virus senstive sugarcane cultivar by using Agrobacterium tumefaciens-mediated transformation method. Transgenic plants were challenged by inoculating with SCSMV. Results showed that though all of the transgenic lines were infected by SCSMV, but the mosaic symptoms appeared on the leaves were significantly milder than that on the wild type. All transgenic shoots showed significantly lower viral loads and attained greater heights than wild-type shoots. This research provided a new pathway for breeding new varieties of sugarcane with virus resistance.